Klauzula zakazu nadużycia praw jako quasi-wyjątek od konieczności ochrony praw jednostki. Rozważania z perspektywy uniwersalnego systemu ochrony praw człowieka - Wiczanowska, Hanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The prevention of the abuse of rights is a legal instrument which aims at the protection of the spirit of law associated with the basic principles of a democratic system. Nevertheless its application sometimes leads to a decreasing effectiveness of the protection of human rights, and sometimes turns against democracy itself and the rule of law. The objective of this analysis is to consider the possibility of the optimalization of using application of such provision from the angle of the effective protection of individuals’ rights. The article has been prepared on the basis of dogmatic methodology with elements of historical analysis. The results of the analysis can contribute to the elaboration of a systemic approach towards the prevention of rights abuse with benefits for the protection of individual rights as well as foreseeability of law.
Prohibition of the abuse of rights as a quasi-exception from the necessity of the protection human rights: considerations from the perspective of the universal system of human rights
Keywords: prohibition of abuse of rights; human rights; democracy; universal system